Recent Trends in HRM : A Qualitative Analysis Using AHP - Joshi, Akashdeep; Sunny, Nita; Vashisht, Sakshi (Prabandhan: Indian Journal of Management, 2017)
In the proposed study, recent trends in Human Resource Management were qualitatively analyzed using AHP. AHP is a technique for analyzing diverse opinions in order of their endorsement by various experts. It is also used in analyzing complex group decision making and is based on the principles of mathematics & psychology (Analytic Hierarchy Process, n.d.). For this purpose, four industry experts’ opinions were analyzed using AHP. In addition to this, existing academic review on recent trends in HRM was scrutinized to develop a list of recent trends in HRM. The role of HRM has shifted from purely administrative function to a strategic core competency in an organization. To recruit and retain quality employees has altogether become more challenging in the present competitive labour market. The present economic changes have acted as a catalyst for the introduction of new HR practices across organizations. So, the changing Indian economic scenario made it important to analyze changes in HRM trends in India. Finally, practical implications based on the findings of the study were discussed. The paper offered a novel way to analyze changing trends in HRM using AHP.